2016
DOI: 10.1007/s11266-016-9757-5
|View full text |Cite
|
Sign up to set email alerts
|

NGOs in the News: The Road to Taken-for-Grantedness

Abstract: establecimiento de una categoría clara en los medios de comunicación sirvió para impulsar el reconocimiento cognitivo de las ONG, y que la cobertura de los medios aumenta la formación de identidad organizativa y la legitimidad de un sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 82 publications
(122 reference statements)
0
10
0
1
Order By: Relevance
“…Nongovernmental organizations (NGOs) are a special type of interest group. The 1970s and 1980s were witness to an explosive growth in the number of nongovernmental organizations (NGOs), yet not until the 1990s did the organizations become publicly recognized as a sector rather than individual activist organizations (Marberg et al 2016 ). Different interest groups operate under different ideologies and will have different targets.…”
Section: Hypothesesmentioning
confidence: 99%
“…Nongovernmental organizations (NGOs) are a special type of interest group. The 1970s and 1980s were witness to an explosive growth in the number of nongovernmental organizations (NGOs), yet not until the 1990s did the organizations become publicly recognized as a sector rather than individual activist organizations (Marberg et al 2016 ). Different interest groups operate under different ideologies and will have different targets.…”
Section: Hypothesesmentioning
confidence: 99%
“…Development NGOs in the UK have been increasingly recognised as a sectorthat is a collection of similar organisations that share similar purposes, challenges, personnel and funding sourcessince the early 1990s. Their own sectoral representative (Bond) was established in 1993, at the same time as the development studies community began looking to civil society organisations to "make a difference" in development (Edwards and Hulme 1992;Marburg, van Kranenburg, and Korzilius 2016). Yet research has been slow to take a sector-wide perspective to understanding development NGOs in Northern (donor) contexts.…”
Section: Methodological Thinking On a Systematic Mapping Process Of Dmentioning
confidence: 99%
“…The year 1990 was selected as a starting point for the research because the 1990s marked the beginning of greater NPO and NGO activity and participation globally (Charnovitz, ; Marberg, Van Kranenburg, & Korzilius, ). Two decades of articles were deemed appropriate for the study; previous research has indicated that this time frame is sufficient for thematic analysis (e.g., Anheier, ; Brudney & Kluesner, ).…”
Section: Methodsmentioning
confidence: 99%